Implementasi Sistem Informasi Pengelolaan Aset Sekolah Berbasis Website pada SMK Islamiyah Ciputat - Ahmad Rio Martin; Arini Vania; Muhamad Faiz Fakhir (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
SMK Islamiyah Ciputat is currently facing challenges in managing school assets, which are still handled manually using Microsoft Excel. This approach triggers operational issues, such as difficulties in data retrieval, a high risk of human error, data duplication, and delays in reporting. This study aims to design and implement a website-based asset management information system to enhance data efficiency and accuracy. The system is developed using the Laravel framework and SQLite database, while applying the Role-Based Access Control (RBAC) method to ensure secure user access. The research results indicate that the developed system successfully integrates data recording, borrowing, asset condition monitoring, and automated report generation. By transitioning from conventional methods to a more structured and transparent digital system, school asset management has become significantly more effective. The implementation of this system is expected to support better decision-making by the school regarding future asset planning and maintenance, while minimizing the risk of loss or damage to unmonitored inventory. This transformation serves as a strategic step in supporting the modernization of administrative governance at SMK Islamiyah Ciputat.